A Communication-Ecological Account of Groups - Kurilla, Robin (Frontiers in Psychology, 2022)
This article presents a novel conception of groups and social processes within and among groups from a communication-ecological perspective that integrates approaches as different as Garfinkel’s ethnomethodology, Heideggerian praxeology, and Luhmann’s systems theory into an innovative social-theoretical framework. A group is understood as a social entity capable of collective action that is an object to itself and insofar possesses an identity. The elementary operations of groups consist in social processes with communicative, pre-communicative, and non-communicative episodes. Groups operate in a number of environments that are conceived of as both correlates of their own processes and providing groups with the raw materials for the fabrication of their constituents. These environments include but are not limited to spatial, discursive, emotional, institutional, semiotic-medial, psychic-personal, technical, and groupal environments. The article paves the way to combine studies on intergroup and intragroup communication in one comprehensive theoretical framework situated on such an abstract level that it can be concretized in view of utterly different cultural contexts and the emic perspectives of actors therein. Accordingly, the framework provides researchers with the conceptual devices to balance the comparability of different lifeworlds with the faithfulness to actors’ inside views. The methodological implications laid out in this article prioritize qualitative, especially ethnographic methods as a starting point for research on group communication.